Creative Approaches in Product Design - Abdalla, Hassan S.; Salah, F. (Cranfield University Press, 2009)
This research paper presents a knowledge-based system for creative design tools (CDT). The main aim of the developed CDT system is to provide designers with a flexible creative design environment to enhance their creative design thinking. Several creative thinking tools are developed and integrated with constructive knowledge databases to widen the search space and expand the design domain. CDT incorporates: a user interface, creativity tools, knowledge databases and five design modules namely: preparation, concept generation, design development, evaluation, and detailed design. A case study is discussed and demonstrated to validate the developed system.
Organised by: Cranfield University
Keywords: Creative design; Design computation; Creative design tools; Product design; Knowledge-based systems